Thin-Layer Drying Model, Drying Rate, and Effective Water Diffusion Coefficient of Pelleted Feed - Wei Wang; Jiyuan Chen; Nan Jin; Hongying Wang; Liangju Wang; Junhua Wu (International Journal of Chemical Engineering)
In this study, classic thin-layer drying models such as the Page model, Verma model, and Two-term model were used to fit the thin-layer drying data of feed. Based on this, a novel thin-layer drying model for pelleted feed (modified Verma model) was proposed. The results indicate that the new model is the optimal choice for describing the drying kinetics of pelleted feed for growing pig and calf. The drying rate of pelleted feed is linearly correlated with the feed moisture content. The effective water diffusion coefficient for pelleted feed of growing pig and calf ranges from 1.86 × 10−10 to 2.75 × 10−9 m2/s and 3.32 × 10−10 to 3.87 × 10−9 m2/s, respectively. The activation energy (Ea) for moisture diffusion in both types of feed is 26.42 kJ/mol and 25.86 kJ/mol, respectively. By establishing predictive models for model parameters based on air temperature and air velocity variables, the new model demonstrates extrapolation capability, wide applicability, and practical value. This work lays the foundation for developing a similarly characterized deep-bed cooling drying model for pelleted feed.